Urban climate resilience in Africa: A review of nature-based solution in African cities' adaptation plans - Kiribou, Razak; Dejene, Sintayehu; Bedadi, Bobe; Ntirenganya, Elie; Ndemere, Julius; Dimobe, Kangbéni (Springer, 2024)
Cities are globally exposed to climate change effects, which revealed that 55% of the world's population is at risk. Despite their low contribution to global greenhouse gas emissions, African cities are paying the highest cost of the threats caused by climate change due to their rapid urban community growth, high population density, and inadequate urban planning. This review has explored and demonstrated the benefit of Nature-based Solutions (NbS) implementation for urban climate crisis resilience that have been implemented globally for sharing information on sustainable city planning in Africa. The analysis is based on the African countries’ Nationally Determined Contribution (NDC) reports, the institution’s review, and scientific articles. The successful implementation of NbS since 2015 in developed countries confirms that NbS has a multi-functional environmental benefit for urban and pre-urban populations. It reduces cities' vulnerability to climate threats and advances numerous Sustainable Development Goals (SDGs) achievement. It revealed only 15 (27,7%) African countries have implemented NbS with 119 projects to adapt and tackle climate change in water, agriculture, forest and woodland, coastal and marine habitat, grassland, and mountain habitat sectors. Rural areas are paid more attention than cities despite the rapid urbanization in the face of extreme climate effects. Furthermore, the review process observed some challenges in translating the approaches of NbS into measurable actions for African urban climate resilience: (i) issues in the governance of urban planning and policies; (ii) insufficient mobilization of resources and lack of private sector involvement in financing NbS; and (iii) lack of comprehensive evidence-based strategies and knowledge for successful operationalization of NbS in African cities.